2013
DOI: 10.1007/s10126-013-9504-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Method for Chromatin Immunoprecipitation Assays in the Marine Invertebrate Chordate Ciona

Abstract: Chromatin immunoprecipitation (ChIP) assays allow the efficient characterization of the in vivo occupancy of genomic regions by DNA-binding proteins, and thus facilitate the prediction of cis-regulatory sequences in silico and guide their validation in vivo. For these reasons, these assays and their permutations (e.g., ChIP-on-chip, ChIP-Sequencing) are currently being extended to several non-mainstream model organisms, as the availability of specific antibodies increases. Here we describe the development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…We had tested in previous studies some of the putative Ci-Bra binding sites identified in notochord CRMs for their ability to be bound in vitro by Ci-Bra via electrophoretic mobility shift assays (EMSA) (Table 1); here we assessed the occupancy of these sites in vivo through ChIP assays on mid-tailbud stage embryos (Figure 8A) using a polyclonal Ci-Bra antibody (Figure 8B) [46]. To test the specificity of the binding by Ci-Bra, we carried out ChIP over a 10-kb stretch encompassing part of the Ci-FCol1 locus and its neighboring gene (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We had tested in previous studies some of the putative Ci-Bra binding sites identified in notochord CRMs for their ability to be bound in vitro by Ci-Bra via electrophoretic mobility shift assays (EMSA) (Table 1); here we assessed the occupancy of these sites in vivo through ChIP assays on mid-tailbud stage embryos (Figure 8A) using a polyclonal Ci-Bra antibody (Figure 8B) [46]. To test the specificity of the binding by Ci-Bra, we carried out ChIP over a 10-kb stretch encompassing part of the Ci-FCol1 locus and its neighboring gene (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Colored boxes below the graph symbolize exons (green, gene KH.C7.121; grey, 5′-UTR; pink, Ci-FCol1 ); the lines connecting them represent introns. (B) Fluorescence microphotograph of a late tailbud Ciona embryo carrying the Ci-Bra>GFP transgene [27], immunostained with the Ci-Bra-specific antibody [46]. The nuclei of the 40 notochord cells are stained by the antibody in red; GFP expression is detected in a subset of the 40 notochord cells, owing to mosaic incorporation of the transgene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in the case of Lmx1-r , we employed an in vivo trans -activation assay to verify the results obtained through the cis -regulatory analysis, taking advantage of the notochord-specific expression of Ci-Bra 28 and of a Ci-Bra-specific antibody developed in our lab 57 , 80 . We used the 2.6-kb Foxa.a promoter region to drive ectopic expression of Ci-Bra in endoderm and CNS precursors ( Foxa.a>Bra plasmid 81 ) and verified the expression of the Ci-Bra protein and the incorporation of the CRMs fused to the LacZ reporter through double immunostaining with the Ci-Bra antibody (Fig.…”
Section: Resultsmentioning
confidence: 99%